Encarnação e transcendência: Gabriel Marcel e o mistério da (co)existência - Cruvinel, Gustavo Henrique Rondis (2023)
The central objective of this work is to scrutinize, through the work of Gabriel Marcel (1889-1973), the theme of incarnation and transcendence. In fact, this is the central point of the author's entire philosophy: the incarnation as the concrete existential condition of the human being in the world in a real perspective of transcendence. To do so, we will seek, here, to reconstitute this related theme starting from a critique of modern rationalism and scientism; This criticism was taken up by the reported French philosopher through the phenomenological-existential theory of the body as an ontological mystery. In this sense, Marcel reconfigures the notion of mystery through a basic ontological interrogation that involves the question for the being (existence) of the one being questioned, man. Therefore, questioning what being is, is the same as asking yourself: who am I? Therefore, in the face of such a question, we arrive at the revelation of existence as incarnation (“I am my body”). Incarnation manifests itself, hic et nunc, as the most tangible data of existence, the point from which the human being participates in the world, the most palpable sign of an opening to an ontological communion, projecting itself as mediation between the I, the world and others (intersubjectivity). In short, this preliminary reach from Marcel's meditations on the body itself as an experience of being leads precisely to an ontological question (mystery of being), which consequently refers us to the world, the other and the transcendent at the heart of existence as coexistence. Such coexistence is revealed to us immediately and unmistakably in the very terms of an awareness of the I in a body, in a radical movement of transcendence. The body reveals itself, in this context, as a being of phenomenon, the maximum expression of a living mystery, ontological communion with the world and with others as, therefore, an originally carnal participation. It is in this perspective that the phenomenon of incarnation and transcendence make up the ultimate meaning of coexistence insofar as, for Marcel, to be (esse) is to coexist (coesse).